2022
DOI: 10.2209/tdcpublication.2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Leukoplakic Oral Squamous Cell Carcinoma Using 4NQO-induced Rat Tongue Cancer Model: Study Utilizing Fluorescence Intensity and Histopathological Evaluation

Abstract: Early identification of leukoplakic oral squamous cell carcinoma (OSCC) is difficult. The purpose of this study was to determine whether it was possible to detect change from normal epithelium to leukoplakic OSCC using a fluorescence visualization (FV) device in a 4-nitroquinoline 1-oxide (4NQO) -induced rat tongue cancer model. If successful, this would facilitate early detection of OSCC. The rats (3 groups of 5) were administered 50 ppm 4NQO in their drinking water over a period of 10, 15, or 20 weeks. Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Kosugi et al [ 37 ] quantitatively evaluated the changes in FI during progression in the transformation from normal epithelium to SCC in rats and reported that the FI variability increased with progression. Masuda et al reported that fluctuations in FI can distinguish normal epithelium from low-grade dysplasia [ 38 ]. Kosakai et al reported that SCC showed an uneven luminosity, while OLP showed a uniform decrease in luminosity [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kosugi et al [ 37 ] quantitatively evaluated the changes in FI during progression in the transformation from normal epithelium to SCC in rats and reported that the FI variability increased with progression. Masuda et al reported that fluctuations in FI can distinguish normal epithelium from low-grade dysplasia [ 38 ]. Kosakai et al reported that SCC showed an uneven luminosity, while OLP showed a uniform decrease in luminosity [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…[99] Figure 10c presents a schematic of the fabrication of functional nanotubes and a schematic of the Raman probe for detecting the oxygen content of cancer cells, where (ii) presents a comparison of the oxygen levels at different depths detected by nanoprobes in a mouse model. [100] The characteristics of SERS with fibers and NPs were incorporated into one unit in the above studies. With deep tissue penetration in SERS detection, concurrent SERS detection modalities have complementary power in pre-and intraoperative resections.…”
Section: Combination With Fiber and Nanoparticles (Nps)mentioning
confidence: 99%
“…c) Schematic of the synthesis for the functional nanoprobe and the operating principle of the nanoprobe to detect oxygen levels in cancer cells. [100] Copyright 2023, John Wiley and Sons. Table 2.…”
Section: Exosomesmentioning
confidence: 99%
See 1 more Smart Citation